2012
DOI: 10.1586/erv.12.72
|View full text |Cite
|
Sign up to set email alerts
|

Safety of seasonal influenza and influenza A (H1N1) 2009 monovalent vaccines in pregnancy

Abstract: Inactivated influenza vaccines have been given to pregnant women since 1964. Since 2004, the Advisory Committee on Immunization Practices has recommended that pregnant women receive trivalent inactivated influenza vaccine at any time during pregnancy. Studies conducted before 2009 did not identify any safety concerns after trivalent inactivated influenza vaccine in mothers or their infants. During the 2009-2010 influenza A (H1N1) influenza vaccination program, several monitoring systems were established or enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Despite recommendations that pregnant and expecting women receive the trivalent inactivated influenza vaccine, [1][2][3] racial and ethnic minority groups have significantly lower rates of immunization, as well higher rates of influenza-related deaths and complications, as compared with Whites. [4][5][6][7] Black/African American as well as Hispanic pregnant women and infants experience a higher burden of morbidity, mortality, and hospitalizations due to influenza.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recommendations that pregnant and expecting women receive the trivalent inactivated influenza vaccine, [1][2][3] racial and ethnic minority groups have significantly lower rates of immunization, as well higher rates of influenza-related deaths and complications, as compared with Whites. [4][5][6][7] Black/African American as well as Hispanic pregnant women and infants experience a higher burden of morbidity, mortality, and hospitalizations due to influenza.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of seasonal 32 and pandemic 33,34 influenza vaccination in the United States and abroad suggest that exposure to the influenza vaccine during pregnancy does not appear to be associated with obstetric or fetal complications. [35][36][37][38] In fact, maternal immunization may reduce rates of preterm birth and suboptimal growth among infants of vaccinated mothers. 39,40 In a landmark randomized controlled trial published in 2008, Zaman and colleagues demonstrated that maternal influenza vaccination confers neonatal protection against influenza, 41 presumably due to transplacental passage of maternal IgG antibody to the fetus.…”
Section: Influenzamentioning
confidence: 99%
“…67,87 Reassuringly, patients' focus on potential vaccine harm comes at a time of growing data about the benefits and safety of maternal vaccination for babies. 32,33,35,[39][40][41] Emphasizing the benefits of maternal immunization, including its safety and absence of fetal harm, should help decrease the perceived cost of maternal immunizations.…”
Section: Concerns About Vaccine Safety and Side Effectsmentioning
confidence: 99%
“…[1][2][3][4] The American College of Obstetricians and Gynecologists (ACOG) and the Advisory Committee on Immunization Practices (ACIP) recommend that pregnant women (and women who expect to be pregnant during the influenza season) receive the trivalent inactivated influenza vaccination. 1,2 Yet, vaccination rates among racially and ethnically diverse pregnant women are significantly lower than those of whites despite persistently higher rates of morbidity, mortality, and hospitalizations due to influenza.…”
Section: Introductionmentioning
confidence: 99%